2023
DOI: 10.1002/jum.16249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Diabetic Kidney Disease Using Ultrasound Localization Microscopy: A Feasibility Study

Abstract: ObjectiveThe purpose of this study is to detect the hemodynamic changes of microvessels in the early stage of diabetic kidney disease (DKD) and to test the feasibility of ultrasound localization microscopy (ULM) in early diagnosis of DKD.MethodsIn this study, streptozotocin (STZ) induced DKD rat model was used. Normal rats served as the control group. Conventional ultrasound, contrast‐enhanced ultrasound (CEUS), and ULM data were collected and analyzed. The kidney cortex was divided into four segments, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…US SRI, also called ultrasound localization microscopy (ULM) [ 17 ], can capture images and track the movement trajectory of microbubbles at an extremely high speed (500 frames/s) over a very short period (several seconds) [ 18 ], automatically generating microvascular images of living tissues. SRI technology can improve the resolution of blood vessels, with a spatial resolution of 100 μm, and the results of the present study showed that the tiny blood vessels near the renal capsule were clearly visible ( Figure 1 D,E).…”
Section: Discussionmentioning
confidence: 99%
“…US SRI, also called ultrasound localization microscopy (ULM) [ 17 ], can capture images and track the movement trajectory of microbubbles at an extremely high speed (500 frames/s) over a very short period (several seconds) [ 18 ], automatically generating microvascular images of living tissues. SRI technology can improve the resolution of blood vessels, with a spatial resolution of 100 μm, and the results of the present study showed that the tiny blood vessels near the renal capsule were clearly visible ( Figure 1 D,E).…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 , 53 , 54 , 55 ] Disregarding the inapplicability of the aforementioned techniques, our study's findings align with several preceding CEUS, MRI, and super‐resolution USI studies with the same or similar AKI and DKD preclinical models. [ 32 , 56 , 57 , 58 ] Instead, we exploited eGFR, a clinically‐prevalent parameter, as a cross‐validative measure of kidney perfusion. The correlation between eGFR and nephropathy under AKI and DKD is well established in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Better resolution can be possibly achieved through super‐resolution localization techniques, although this may come at the cost of increased acquisition time and require the use of contrast agents. [ 56 , 62 ] With improved resolution, we might be able to directly observe glomerular and tubular pathogenesis. Moreover, the current linear scanning method results in anisotropic resolutions in the cross‐sectional and elevational directions.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS), used in clinics, is often unable to distinguish early kidney disease from the healthy kidney; instead, the MB pattern is used to differentiate solid renal tumors from pseudo-tumors [58]. Zhang et al showed no significant differences in renal perfusion using CEUS on a streptozotocininduced DKD rat model compared with healthy controls [23]. Other imaging modalities have shown to be limited in resolution as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SRUS showed a superiority to ultrasound in the evaluation of human kidney allograft vascularization [19]. Additionally, SRUS has been used on rodent kidneys to detect decreased vascular density after acute kidney injury and flow-velocity changes [20][21][22][23]. However, altered renal vascular morphology as a consequence of DKD development has not previously been investigated using SRUS.…”
Section: Introductionmentioning
confidence: 99%